How Big Data, Comparative Effectiveness Research, and Rapid-Learning Health-Care Systems Can Transform Patient Care in Radiation Oncology - Sanders, Jason C.; Showalter, Timothy N. (Frontiers in Oncology, 2018)
Big data and comparative effectiveness research methodologies can be applied within the framework of a rapid learning health care system to accelerate discovery and to help turn the dream of fully personalized medicine into a reality. We synthesize recent advances in genomics with trends in big data to provide a forward-looking perspective on the potential of new advances to usher in an era of personalized radiation therapy, with emphases on the power of rapid learning health care systems to accelerate discovery and the future of individualized radiation treatment planning.